Sustainable Tourism Management at EcoMangrove Ulam Sari Kedonganan - JULIANTARA, I Wayan Juliantara; Dearestu Putty N; SURLIMNA, Ni kadek Linda Surlimna; FRANZA, Ni Putu sinria; G Oka Baskara JW; LAKSMI, Putu Ayu Sita (PT Batara Swastika Harati, 2024)
The Ecomangrove Ulamsari Kedonganan tourist attraction is one of Bali's ecotourism destinations, offering educational and recreational experiences in a mangrove forest area. The increasing number of visitors poses potential negative impacts on the environment and society. This service aims to analyze sustainable tourism management at Ecomangrove Ulamsari Kedonganan. The findings show that sustainable tourism management at Ecomangrove Ulamsari Kedonganan is still not optimal. The ecological, economic, and socio-cultural aspects need to be better integrated. The ecological aspect has yet to be fully implemented in waste management, wastewater treatment, and carrying capacity. The economic aspect could have been more optimal in increasing local income and equitable economic benefits. The socio-cultural aspect has yet to be fully applied in local community empowerment and cultural preservation. Based on the findings, several strategies are recommended to improve sustainable tourism management at Ecomangrove Ulamsari Kedonganan:1. Implementing better waste and wastewater management systems, 2. Developing more creative and innovative ecotourism, 3. Increasing local community participation in ecotourism management, 4. Strengthening education and awareness for tourists about ecotourism